0204 Advantage Of Single-effort Ultra-marathons To Examine Homeostatic Loads And Circadian Properties Of Human Endurance Under Total Sleep Deprivation. (27th April 2018) - Choynowski, J; Kim, J; Capaldi, V; Agnew, J; Hammer, S; Brager, A
Abstract: Introduction: There a few field studies that have examined human performance dynamics under total sleep deprivation. Here, the logistics of a single-effort ultra-marathon provided us with the opportunity to dissect the homeostatic loads and circadian properties of human endurance across a 100-mile race. Methods: Race data was collected from 50-mile and 100-mile race efforts in the Florida swamps (Panhandle) and tropics (Keys) during the months of March - May in order to construct a 24-hour human performance response curve (hPRC). We also focused on the "recovery" phase of preparation for single-effort ultra-marathons to identify homeostatic properties of (self-reported) sleep needs following intense exercise. Results: Average race pace was 15.1 ± 2.3 min/mile with each race starting near sunrise (ZT 0). Between sunrise (ZT 0) and sunset (ZT 12), race pace was slower over time peaking at 18 min/mile near sunset. After sunset, race pace returned to the average race pace. The slowest pace across the total 25.2 ± 3.8 h of racing happened mid-night (ZT 20 - 22), dropping down to 22 min/mile, before gradually returning to the average race pace. The ultra-runners averaged 6.8 + 0.2 h of nighttime sleep during training and after the race. Reports of sleep disturbances were 2-fold greater during training for longer single-effort races. Few runners napped. 46% of runners identified as 'extreme' larks. Conclusion: To conclude, we were successfully able to map diurnal patterns of human performance sensitive to homeostatic loads and chronobiology under total sleep deprivation in a field study. Support (If Any): F32HL116077 Department of Defense Military Operational Medicine Program